Olanzapine induced DVT: A Case Report - Joshi, N; Singh, PM; Thapa, M; Gautam, S (Journal of Psychiatrists’ Association of Nepal, 2014)
Deep Vein Thrombosis (DVT) is a serious life threatening event which might not be paid much attention in Psychiatric setting. In this paper, a case of DVT following the use of Olanzapine is presented. The patient was in good general physical health and had no personal or familial history of DVT. There were no known risk factors for DVT. The patient was not overweight (BMI < 25) but she suffered from DVT after initiating Olanzapine. Conclusion: Risk of DVT exists in patients under treatment with atypical antipsychotics in spite of no pre existing risk factor. DOI: http://dx.doi.org/10.3126/jpan.v3i1.11351 J Psychiatrists’ Association of Nepal Vol .3, No.1, 2014: 41-42